Opportunities and Challenges for Reinforcing Organic Agriculture Research Capacity in East African Universities: Experience of Makerere University - Kabi, Fred; Nalubwama, Sylvia; Kabi, Samuel; Kwikiriza, Norman; Anecho, Stephen; Kiggundu, Muhammad (African Organic Conference, 2015)
There is a need for generation of new knowledge and skills to reinforce organic agriculture capacity to answer a variety of lingering questions about production, product quality, marketing, social economic implications on livelihoods and sustainable development through research. Generated knowledge is also needed to inform development and institutionalization of national policies on organic agriculture. Support to universities in collaboration with the private sector to popularize and commercialize organic agriculture through curriculum review and regional harmonization will help to produce a critical mass of competent graduates to promote organic agriculture. At Makerere University we believe great success in the subsector will only come from great support.
Keywords: Opportunities; East African Universities; Social economic; Crop production